Experimental evaluation of plasticity-induced crack shielding from crack tip displacements fields - J.M. Vasco-Olmo; F.A. Díaz (Fracture and Structural Integrity)
In this work it is proposed a methodology for the evaluation of plasticity-induced crack shielding from the analysis of the crack tip displacements fields measured by digital image correlation. This methodology is based on the evaluation of the stress intensity factors determined from the displacements fields measured at the vicinity of the tip of a growing fatigue crack. For the characterisation of the crack tip displacements field, CJP model has been implemented. This model considers the shielding effects due to plasticity generated during fatigue crack growth. For the purpose of the current work, several fatigue experiments at different R-ratios have been conducted on Al2024-T3 compact tension specimens. In addition, compliance based methods have been adopted to perform a comparison of the results with those obtained by DIC. Results show a good level of agreement, illustrating the enormous potential of DIC technique for the study of fracture mechanics problems.